The Using Miniature Traditional Houses on Increasing Understanding of the Concept of Socio-Cultural Diversity - Rahmawati, Anisah; Tetep; Mulyana, Eldi (Institut Pendidikan Indonesia, 2023)
Indonesia is rich in diversity, which makes the teaching materials more numerous, causing students' understanding of the concept of socio-cultural diversity to be low. This research has the objective of examining the influence of miniature traditional houses on increasing the understanding of the concept of socio-cultural diversity among students at SMPN 5 Garut. The research method used was a quasi-experimental study with a